Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/ef800499x
|View full text |Cite
|
Sign up to set email alerts
|

Mesophase from Anthracene Oil-Based Pitches

Abstract: This work deals with the preparation of the mesophase from two pitch-like materials obtained from anthracene oil by oxidative thermal condensation (AOP-1) and the subsequent thermal treatment and distillation of AOP-1 (AOP-2). The mesophase was obtained by the controlled pyrolysis (440-470 °C and different periods of residence times) and subsequent sedimentation of the samples. In the case of the pitch prepared by oxidative thermal condensation, a dynamic pressure of 5 bar was applied during the pyrolysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…An anthracene oil supplied by a local company was submitted to air-blowing at moderate temperatures, then thermally treated under inert atmosphere at around 400°C and vacuum-distilled to obtain a pitch-like material [25][26][27]29]. This was then subjected A c c e p t e d M a n u s c r i p t 4 to further heat-treatment at 430°C for 3h under inert atmosphere and the mesophase part of the pitch was separated via sedimentation [30].…”
Section: Activated Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…An anthracene oil supplied by a local company was submitted to air-blowing at moderate temperatures, then thermally treated under inert atmosphere at around 400°C and vacuum-distilled to obtain a pitch-like material [25][26][27]29]. This was then subjected A c c e p t e d M a n u s c r i p t 4 to further heat-treatment at 430°C for 3h under inert atmosphere and the mesophase part of the pitch was separated via sedimentation [30].…”
Section: Activated Carbonmentioning
confidence: 99%
“…In this work we report on the use of a coal-tar-derived activated carbon for the treatment of an industrial wastewater in which the contaminants present were found to be mainly benzene and toluene. The precursor of the activated carbon used in this study was obtained by the distillation of coal-tar, and has been the object of extensive research by our group [25][26][27]. Chemical activation of the treated pitch gives rise to activated carbons with very high surface areas (up to 2,700 m 2 /g) and large pore volumes [28].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the heat-soaking temperature from 420 to 430 °C, bulk liquid crystalline mesophase with a flow texture is present in the anthracene-derived mesophase pitch as shown in Figure a, and the anisotropic content sharply increases from 17 to 100 vol %. It is obvious that the formation and development of bulk liquid crystalline mesophase has experienced a process of generation, growth, coalescence, deformation, and disintegration of mesophase spheres upon heat treatment. , The liquid crystalline spheres have enough time (4 h) to complete the conversion process (i.e., nucleation, growth, coalescence, deformation, and disintegration) at such a high temperature (providing essential energy). ,, Combined with the acceptable softening point of 280 °C, anthracene can undoubtedly be used as a suitable precursor for preparing high-quality mesophase pitch heat treatment at a temperature range of 420 and 430 °C, which agrees well with the previous studies in the literature. , In contrast, the mesophase pitch products prepared from naphthalene synthetic pitch, coal tar-based impregnating pitch, and C 5 –C 9 aromatic hydrocarbons still exhibit an initial mesophase behavior as shown in Figure b–d. The optical texture of C 5 –C 9 aromatic hydrocarbons-derived mesophase pitch heat-soaked at 430 °C is similar to that of anthracene-derived mesophase pitch heat-soaked at 420 °C, which implies that the bulk mesophase will be formed if further increasing the soaking temperatures (or prolonging the soaking time).…”
Section: Resultsmentioning
confidence: 99%
“…7,10,29 Com- bined with the acceptable softening point of 280 °C, anthracene can undoubtedly be used as a suitable precursor for preparing high-quality mesophase pitch heat treatment at a temperature range of 420 and 430 °C, which agrees well with the previous studies in the literature. 29,30 In contrast, the mesophase pitch products prepared from naphthalene synthetic pitch, coal tar-based impregnating pitch, and C 5 − C 9 aromatic hydrocarbons still exhibit an initial mesophase behavior as shown in Figure 5b−d. The optical texture of C 5 − C 9 aromatic hydrocarbons-derived mesophase pitch heatsoaked at 430 °C is similar to that of anthracene-derived mesophase pitch heat-soaked at 420 °C, which implies that the bulk mesophase will be formed if further increasing the soaking temperatures (or prolonging the soaking time).…”
Section: Energy and Fuelsmentioning
confidence: 97%
“…The mesophase pitch was traditionally prepared by direct thermal condensation method [19][20][21] which had some advantages, such as simple process and operation. However, it had special requirement on feedstock's structure and equipment material.…”
Section: Introductionmentioning
confidence: 99%